Does a lateral tibial plateau fracture (Takeuchi type III) occuring during opening wedge high tibial osteotomy induce a higher revision rate to total knee arthroplasty - Giardini, Piero; De Luca, Lapo; Crespan, Beatrice; Christodoulidis, Avraam; Molinari, Marco (Acta Biomedica Atenei Parmensis, 2022)
Background and aim: High tibial osteotomies (HTO) are effective procedures to treat younger patients affected by moderate but symptomatic arthritis. Open-wedge HTO (OW-HTO) is more often performed compared to a closing wedge osteotomy to treat varus arthritis of the knee due to a lower incidence of complications and better results: lateral hinge fracture (LHF) is the most common complication of OW-HTO. Intra articular fractures of the lateral tibial plateau (Takeuchi type III) appear as a particularly serious complication due to its extension to the subchondral bone of the compartment towards which the load is shifted. Aim of our study, is to assess if an intra articular fracture of the lateral tibial plateau occurring during an OW-HTO leads to an higher risk of failure and to an early conversion to a total knee arthroplasty. Methods: Between January 2013 and December 2018 114 patients underwent OW-HTO at our Orthopaedic Department. All the patients underwent the same surgical procedure performed by a skilled knee surgeon: a subcutaneous-medial locked plate (Tomofix®, Synthes, Solothurn, Switzerland) has been used in all the procedures to stabilize the osteotomy. Clinical and radiographic follow up has been performed at one, three, six and twelve months postoperatively afterwards annually. We retrospectively reviewed all the intra operative fluoroscopy of patients to detect those affected by an intra articular fracture of the lateral tibial plateau occurred intra operatively. Results: A LHF occurred in 11 out of 114 patients (9.65%) who underwent an OW-HTO; in particular nine patients (7.9%) had a Type III LHF. In all cases such complication has been detected intra operatively. In the subgroup of patients who experienced an intra articular fracture of the tibial plateau at the last follow up only one patients underwent to a revision with a total knee arthroplasty; in other words, the survivorship of an OW-HTO complicated by a LHF type III resulted 89% at a mean follow-up of 5 years. In 103 patients without an intraoperative fracture, the percentage of patients free from revision at the last follow up resulted of 92%. Conclusions: Takeuchi type III fracture is an uncommon but serious complication to manage: in our case series we found that an early recognition and a correct treatment of this occurrence don’t lead to a premature conversion to a knee arthroplasty if compared with an uncomplicated osteotomy. Further studies are necessary to establish specific subjective outcomes after OW-HTO burdened by an intra articular fracture of the lateral plateau.